2010
DOI: 10.2119/molmed.2010.00030
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Inflammation-Associated Preterm Birth by Knockdown of the Endothelin-1-Matrix Metalloproteinase-1 Pathway

Abstract: Premature delivery occurs in 12% of all births, accounts for nearly half of neonatal morbidity and is increasing in frequency. Current therapeutic approaches to preterm delivery are ineffective and present serious risks to both the mother and fetus. Although there are multiple factors that contribute to the etiology of preterm birth, the single most common cause is infection. Recently, using cDNA microarray analysis of human placental tissue, we demonstrated that human placental matrix metalloproteinase-1 (MMP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…We sought to determine if the CRTH2 agonist Pyl A had the same tocolytic and feto‐protective effect as 15dPGJ 2 in delaying preterm labour in LPS‐treated mice. A dose–response effect was demonstrated with LPS (serotype 0111:B4) since varying potencies can be seen between serotypes and within batches . Administration of 20 μg LPS led to reliable preterm delivery with the least variation between mice (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…We sought to determine if the CRTH2 agonist Pyl A had the same tocolytic and feto‐protective effect as 15dPGJ 2 in delaying preterm labour in LPS‐treated mice. A dose–response effect was demonstrated with LPS (serotype 0111:B4) since varying potencies can be seen between serotypes and within batches . Administration of 20 μg LPS led to reliable preterm delivery with the least variation between mice (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…The levels of ET-1 and ECE-1 were increased in gestational tissue, and treatment with an ECE-1 inhibitor, ET-1 receptor A antagonist, or ECE-1 RNA interference could prevent preterm delivery in mice [10]. Those authors also reported that upregulation of MMP-1, which is increased during human labor, was inhibited by ECE-1 RNA interference in the mouse model [9]. ET-1 has been reported to be synthesized in the human amnion [11,12], and its concentration in amniotic fluid is approximately 10-to 100-fold higher than that observed in plasma [7].…”
Section: Introductionmentioning
confidence: 93%
“…The level of ET-1 is increased in the amniotic fluid of the forebag, the compartment between the fetal head and the cervix, during labor [7] and increases myometrial smooth muscle tone [8]. Recently, it was reported that the ECE-1/ET-1 pathway plays a critical role in preterm delivery in a mouse model [9,10]. The levels of ET-1 and ECE-1 were increased in gestational tissue, and treatment with an ECE-1 inhibitor, ET-1 receptor A antagonist, or ECE-1 RNA interference could prevent preterm delivery in mice [10].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, endothelin 1, an extremely potent vasoconstrictor peptide (Yanagisawa et al, ) produced by endothelin‐converting enzyme 1 (Rubanyi and Polokoff, ), induces contractile responses in human myometrium (Kaya et al, ). Silencing the endothelin 1 signaling by RNA interference knockdown of endothelin‐converting enzyme 1 prevents the onset of preterm birth and the up‐regulation of MMP1 (Wang et al, ).…”
Section: Regulation Of the Mmp System By Inflammatory Cytokines Hormmentioning
confidence: 99%
“…For example, preterm birth, defined as delivery occurring before the 37th week of gestation, is the most‐significant contributor to neonatal morbidity and mortality. Preterm birth occurs in 12% of all pregnancies, and accounts for more than 50% of long‐term morbidity (Manase et al, ) and 60–80% of perinatal mortality, which is second only to congenital anomalies (Wang et al, ). Preterm birth is thought to be triggered by multiple mechanisms, especially by premature rupture of membranes (PPROM) (Parry and Strauss, ), which can result from the dysregulated activitity of MMPs on the ECM.…”
Section: Introductionmentioning
confidence: 99%